(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
The present research traces a history of the Indian drama from its humble beginnings andgoes on to detail some of the major contemporary Indian dramatists and their works with specialreference to their experimental elements. The data collected from both the primary and secondarysources. Ancient Indian theater has made significant contributions to global literature. Indian dramatistshave produced a wide range of works, each of which is distinctive and wholly evocative of India and itspeople and culture, as well as of the historical and cultural shifts that have taken place there over thecenturies. Modern Indian play may be better understood and appreciated with the aid of this research. Bythe conclusion of the paper, the reader has a solid grasp of the experimental components in the work ofthe chosen contemporary Indian dramatists.